The Concept of Subalternism in Munshi Premchand’s Sevasadan: Unveiling the Subaltern Reality in Munshi Premchand's Sevasadan (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Subaltern in literature has been projected in multiple ways by different writers. Even, Premchand has projected various sections of people in different ways in his novels. Munshi Premchand is one of the major writers in modern Hindi literature. For him, novel is a social and historical document. As a writer, Premchand studies life very minutely and he himself shared the sufferings and problems of the subaltern section of the society in India. He objectively analyses the problems of the subaltern section and he is never satisfied with the mere descriptions. He intends to eradicate those problems which have eaten into the vitals of the lower and the middle class of society. He is the writer who portrays the grim reality of Indian society especially the rural and semi urban settings. Premchand presents the socio-economic and political derivation of the disadvantaged sections of colonial India. This paper gives a brief account to the life of the subalterns as shown in Sevasadan. Subaltern Studies’ assumes a special significance in Indian historiography which is necessary to understand the need of all the subordinated people like peasants, workers, lower caste women and dalits whose voices were seldom recorded before in history, in one way or the other. Therefore, the word ‘subaltern’ will recur in the present study as a term for the general attribute of subordination in the society in terms of caste, color, creed, religion, gender or on the ethnic basis, because of the long history of subjugation of the subalterns.